Long-Term Visual Function Effects of Pan-Retinal Photocoagulation in Diabetic Retinopathy and Its Impact in Real Life - Baptista, Pedro Manuel (2021)
Purpose: To address the long-term visual function after bilateral pan-retinal photocoagulation (PRP) and its impact in real life, namely on visual field (VF) legal criteria to drive. To determine potential predictors related to clinical factors and treatment strategies. Patients and methods: Observational cross-sectional study. Eyes from diabetic patients diagnosed with diabetic retinopathy who underwent bilateral PRP, with or without macular treatments and with visual acuity legal criteria for non-professional driving were randomly assigned. Main outcomes were: demographic and clinical data including best corrected visual acuity; binocular visual field (EBST-Esterman Binocular Suprathreshold Test, Humphrey analyzer3®); contrast sensitivity (CS-Metrovision-MonPack3®); light scattering in the retina (HD Analyzer, Visiometrics®). Results: Seventy-one diabetic patients included (44 men and 27 women), with a mean age of 62.2±11.8 years. PRP was performed, on average, 9.7±6.9 years before the study. The average EBST Score was 85.8±17.0 and the average CS (2-5cpd) was 19.5±2.9 dB in photopic and 14.2±4.1 dB in mesopic conditions. Through a multivariate regression model, after adjusting to the clinical and demographic factors as possible confounders, we found that treatment factors associated with worse results were the use of Argon laser for the EBST Score, the very confluent PRP for the number of non-viewed points in the central 30°x20° of the EBST and the presence of macular treatments for the CS tests. According to Portuguese law, 79% (n=56) of patients had minimal EBST amplitudes for non-professional driving. Conclusion: The functional results achieved in our sample are compatible with an active life, allowing most of the patients included to overcome the requirements of Portuguese legislation for driving light vehicles, namely at the level of the binocular visual field. These results highlight the role of PRP in the treatment of diabetic retinopathy in an era with evolving less aggressive laser options.